3. Find the two x-intercept of "f(x)=x^{2}-3x+2".
Solve the equation "x^{2}-3x+2=0"
"D=b^2-4ac=3^2-4\\cdot 1\\cdot 2=9-8=1;\\\\\n\\sqrt{D}=1;\\\\\nx_1=\\frac{-b+\\sqrt{D}}{2a}=\\frac{3+1}{2}=2;\\\\\nx_2=\\frac{-b-\\sqrt{D}}{2a}=\\frac{3-1}{2}=1."
Answer: b. "x" = 1, 2
4. Compute the first three derivatives of "f(x)=2x^{5}+x^{\\frac{3}{2}}-\\frac{1}{2x}"
Note that "(x^n)'=nx^{n-1}" and "f(x)=2x^{5}+x^{\\frac{3}{2}}-\\frac{1}{2x}=2x^{5}+x^{\\frac{3}{2}}-\\frac{1}{2}x^{-1}" .
We get
"f'(x)=2\\cdot 5x^4+\\frac{3}{2}x^{\\frac{1}{2}}-\\frac{1}{2}\\cdot (-1)x^{-2}=\\\\\n= 10x^4+\\frac{3}{2}x^{\\frac{1}{2}}+\\frac{1}{2}x^{-2}=\\\\\n=10x^4+\\frac{3}{2}x^{\\frac{1}{2}}+\\frac{1}{2x^2};"
"f''(x)=10\\cdot 4x^3+\\frac{3}{2}\\cdot\\frac{1}{2}x^{-\\frac{1}{2}}+\\frac{1}{2}\\cdot (-2)x^{-3}=\\\\\n= 40x^3+\\frac{3}{4}x^{-\\frac{1}{2}}-\\frac{1}{x^3};"
"f'''(x)=40\\cdot 3x^2+\\frac{3}{4}\\cdot(-\\frac{1}{2})x^{-\\frac{3}{2}}-(-3)x^{-4}=\\\\\n=120x^2-\\frac{3}{8}x^{-\\frac{3}{2}}+\\frac{3}{x^4}."
Answer: d. "10x^{4}-\\frac{3}{2}x^{\\frac{1}{2}}+ \\frac{1}{2x^{2}}, 40x^{3}-\\frac{3}{4}x^{-\\frac{1}{2}}- \\frac{1}{x^{3}}, 120x^{2}-\\frac{3}{8}x^{-\\frac{3}{2}}+ \\frac{3}{x^{4}}"
Comments
Leave a comment